2007
DOI: 10.1136/jme.2006.019067
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle, responsibility and justice

Abstract: Both prevention and treatment of obesity are necessary means to reduce risk of severe disease Law, ethics and medicine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(106 citation statements)
references
References 30 publications
0
104
0
2
Order By: Relevance
“…Even if it could be shown that some types of obesity are more subject to will, there are still relevant arguments against differencing access to health care according to responsibility (Cappelen and Nordheim 2005;Feiring 2008). As Mackenzie points out (2011), the obesity category is heavily embedded in social and cultural conceptions.…”
Section: Carlmentioning
confidence: 99%
“…Even if it could be shown that some types of obesity are more subject to will, there are still relevant arguments against differencing access to health care according to responsibility (Cappelen and Nordheim 2005;Feiring 2008). As Mackenzie points out (2011), the obesity category is heavily embedded in social and cultural conceptions.…”
Section: Carlmentioning
confidence: 99%
“…37,38 This understanding, albeit in a slightly different and more moderate form, also resonates with contributions to the debate on lifestyle-related illness that places an emphasis on people's willingness to lead a healthy life, even if they do not succeed. 39, 40 As mentioned above, the conceptual tool aiding those who argue for the exclusion of people with 'high-risk' lifestyles from (some) public health care is risk stratification. Risk stratification is highly relevant to our understanding of solidarity because people's recognition of similarity with others in a relevant respect -which is an important condition for their willingness to carry costs for others according to our definition -can also be based on a common risk that is shared.…”
Section: Solidarity Lifestyle-related Diseases and Individual Responmentioning
confidence: 99%
“…The question of responsibility reflects a concept of justice, in which health inequality that follows from free individual choices is less problematic than inequality that follows from social or random causes [24]. Should a problem that could be solved by the individual deciding to eat less and exercise more be solved by a publicly funded surgical operation?…”
Section: Obesity and Individual Responsibilitymentioning
confidence: 99%